Development of Science Module Integrating Local Wisdom of Biotechnology Materials for Class IX Junior High School - Alifia Nabila, Bunga; Yulinda, Ratna; Febriyani Putri, Rizky (Riviera Publishing, 2023)
The purpose of this research is to describe: (1) the validity of the science module integrating local wisdom on biotechnology, (2) the practicality of the module, and (3) the effectiveness of the module. Module development implements only three stages of the 4D model, namely (define, design, and develop). The instruments implemented in the research include learning achievement tests, student response questionnaires, and science module validation sheets. The research resulted in validating the science module integrating local wisdom from experts who showed very valid criteria by obtaining a score of 3.86. The learning outcomes test in this module is also very valid, with a score of 3.82. The results of the practicality of the module obtained a value of 86.18% which was indicated by efficient criteria. The IPA module integrates local wisdom and is also declared effective by obtaining an n-gain of 0.82 with high criteria. From these results, it can be concluded that the science module integrating local wisdom in the biotechnology material developed can be implemented as teaching material because the test results are feasible and valid.